Strengthening Green Nationalism as a Form of Disaster Mitigation Effort for the Tantan Village Community, Muaro Jambi Regency - Candra, Alif Aditya; Utami, Sundari; Ichsan, Muhammad; Maulia, Siti Tiara; Melisa, Melisa (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
This study aims to strengthen green nationalism as a form of disaster mitigation effort in Tantan Village, Muaro Jambi Regency. Through a participatory and educational approach, the program integrates patriotic values with ecological awareness rooted in local wisdom. The methods employed include public outreach, environmental training, and community mentoring in the sustainable management of natural resources. The results of the activities indicate an increased public understanding of the importance of environmental conservation as part of national responsibility. Furthermore, a shared commitment has been established to face disaster risks through reforestation initiatives, the management of critical lands, and the strengthening of disaster-resilient village institutions. In conclusion, green nationalism can serve as a strategic approach that merges nationalistic spirit with environmental concern to foster more resilient and sustainable rural communities.